2020
DOI: 10.4236/ajps.2020.118083
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Growth and Yield of Two Local Rice Varieties (Tox-728-1 and Madjitolngar) in Response to Indogenous Mycorrhizal Inoculation in South-Chad

Abstract: This study was carried out to find out how dependent are two local rice varieties (Magitolngar and Tox-728-1) to inoculation with selected endogenous arbuscular mycorrhizal fungi (AMF) in a field where they were isolated. The multi-indigenous endomycorrhiza spores previously isolated and identified were the active ingredient in the production of bioinoculants used for this purpose. Spores massively multiplied from the rhizosphere of each rice variety in each of the four locally collected soils substrates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The number of seeds per panicle of the variety Nerica L36 increased for all the densities considered. The same results were found by Nadjilom et al (2020), which showed significant seeds number per panicle of two varieties of Rice with mycorrhized than non-mycorrhized treatment in South-Chad.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The number of seeds per panicle of the variety Nerica L36 increased for all the densities considered. The same results were found by Nadjilom et al (2020), which showed significant seeds number per panicle of two varieties of Rice with mycorrhized than non-mycorrhized treatment in South-Chad.…”
Section: Discussionsupporting
confidence: 82%
“…Comparatively, between the amount, the doses 2, 3 and 4 were significant (P≤0.05) on the number of panicles per plant for density 2 (25 cm x 25 cm). Considering the doses for density 2, the number of panicles per plant varied from 16 to 18 compared to dose 1 (14). Contrarily, the effect of different amounts not influence the number of panicles per plant for the density 1 and 3.…”
Section: Iii14 Number Of Paniclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported that spraying humic acid on leaves of rice of C70 variety had effected in increased productivity and post-harvest quality of rice. Nadjilom et al (2020) reported significant increase in tiller production due to AMF treatment in two African paddy verities viz., Tox-728-1 and Madjitolngar. Working on resource allocation and grain yield as altered by AMF inoculation, Zhang et al (2015) found that AMF inoculation markedly increased biomass allocation to shoots.…”
Section: Discussionmentioning
confidence: 99%
“…A mixture of phosphorus gypsum and manure can reduce soil salinity [18]. The use of mycorrhiza can increase the growth of rice plants under environmental stress conditions [19]. Rice plants also have the ability to reduce salinity levels.…”
Section: Introductionmentioning
confidence: 99%